The Consultant-Client Relationship: A Systems-Theoretical Perspective - David Seidl; Michael Mohe (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
The aim of this paper is to explain consulting failure from a systems-theoretical perspective and to provide a new framework for analysing consultant–client relationships. By drawing on Luhmann's systems theory, clients and consultants are conceptualised as two autopoietic communication systems that operate according to idiosyncratic logics. They are structurally coupled through a third system, the so-called “contact system”, which constitutes a separate discourse. Due to their different logics no transfer of meaning between the three discourses is possible. This contradicts the traditional notion of consulting as a means of providing solutions to the client's problems: neither is the consultant able to understand the client's problems nor is it possible to transfer any solutions into the client system. Instead, consulting interventions only cause perturbations in the client system. Consequently, the traditional functions of consulting are called into question. The paper discusses the implications of this analysis with relation to the traditional approach to consulting, and presents a tentative framework for a systemic concept of consulting.
urn:nbn:de:bvb:19-epub-1920-1
Keywords: M10; 650; Consulting; Consultant-Client Relation; Consulting Failure; Systems Theory